Determinant of Muslim Consumers in Indonesia to Purchase MSMEs Products: Does Halal Certification Matters? - Jeihan Ali Azhar; Fajar Sodik (Yayasan Darussalam Bengkulu, 2025)
Background: Indonesia has the world’s largest Muslim population, which drives strong demand for halal-certified products due to religious obligations. Understanding what influences Muslim consumer behavior is essential. Method: This study adopts a quantitative approach with purposive sampling. Data were collected through surveys in Indonesia during October 2023, yielding 308 valid questionnaires. Analysis was performed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) via SmartPLS 3. The Theory of Planned Behavior (TPB) guided the investigation into factors affecting purchase intentions for halal-certified products from Micro, Small, and Medium Enterprises (MSMEs). Results: Findings show that halal certification, religiosity, subjective norms, halal awareness, consumer satisfaction, and trust significantly influence purchase intentions. Conversely, perceived behavioral control and attitudes do not significantly affect purchase intention. Conclusion: Enhancing halal knowledge and awareness is a key strategy to increase Muslims’ purchase intentions for MSME halal products. Policymakers and halal certification authorities should enforce consistent inspections on MSME products to ensure alignment with Islamic principles, thereby boosting consumer confidence.